Study on Flood Control of the Sumber Pinang River in Sidogiri, Pasuruan Regency through River Normalization, Levees, and Parapet Walls - Imroni Arif; Vita Ayu Kusuma Dewi (Universitas Islam Raden Rahmat, Malang, 2025)
The Sumber Pinang River in Pasuruan Regency frequently experiences flooding due to its insufficient capacity. This study aims to analyze flood control measures using hydrological and hydraulic approaches with the HEC-RAS 6.4.1 software. The data used include maximum rainfall, river cross-section profiles, and land use. The planned flood discharge was calculated using the Nakayasu Synthetic Unit Hydrograph (SUH) method, resulting in a peak discharge of 442.823 m³/s. The analysis results indicate that 81% of the river cross-sections are prone to overflow. Proposed control measures include river normalization and the construction of levees and parapet walls. River normalization is planned for the entire river body, while levees and parapet walls are proposed at critical points to enhance the river's capacity. This study provides recommendations for more effective flood control planning in the future.